Bridging the gap between the sciences and the humanities in Nigeria; the Wale Okediran example (2008)
Contemporary studies in humanistic traditions have revealed that there are certain negative attitudes to humanistic studies in third world countries. The relevance of the humanities, especially literature, to the socio - political and economic challenges of the 21st century remain controversial. The assumption is that literature and indeed other disciplines in the humanities should be classified as ‘recreational studies’. This article examines the place of the humanities, especially literature, within the humanistic tradition. The works of Wale Okediran, a physician, politician and novelist are selected for this study. Okediran’s writings are exemplary in that they are marked with a distinct quality of having been produced by a completely humanized mind.